Estudio y Evaluación de las Tecnologías y Lugares de Aplicación para el Aprovechamiento de Energías Oceánicas Mediante Gradiente Térmico en Santa Marta, Colombia (2022)
ABSTRAC: The ocean is an important source of energy for the earth, and in the field of electricity, ocean energy plays an important role in the energy transition. However, when you want to take advantage of this energy source, you have to consider a number of factors, such as what energy source to use and what technology is economically viable. The purpose of this work is to collect information from studies that analyze the energy potential of the oceans of Santa Marta and understand if there are enough sites available to use thermal gradient energy. In Santa Marta in the study [1] researchers analyzed the continental shelf. Five profiles were selected to investigate and the selected bays were: Taganga, Santa Marta and Gaira. In this study, the bay was found to have a moderate depth of about 150 meters off the coast. The chosen sites show that, on the continental shelf, due to the Sierra Nevada de Santa Marta, which has a topography that originates in its foothills, the features of low slope and uniformity are only present in certain areas of the selected profile, this information. Through the analysis of these studies it is intended to conclude if there are physical conditions and availability of resources to take advantage of the thermal gradient energy in Santa Marta.